This paper presents the effect of extractive and abrasive material of tropical timber (Damar Laut, Mersawa, and Oil Palm wood) and of composite products (Fiber Board and Cement Board) on the wearing of high speed steel and tungsten carbide cutting tools. The extractive content provides a significant contribution on the chemical wearing of the cutting tools. Oil palm wood and Mersawa wood contain extractives which are more corrosive compared to other wood species tested. Mechanical wear resista - Wayan DARMAWAN; Irsan ALIPRAJA (Jurnal Ilmu dan Teknologi Hasil Hutan, 2010)
This paper presents the effect of extractive and abrasive material of tropical timber (Damar Laut, Mersawa, and Oil Palm wood) and of composite products (Fiber Board and Cement Board) on the  wearing of high speed steel and tungsten carbide cutting tools. The extractive content provides a significant contribution on the chemical wearing of the cutting tools. Oil palm wood and Mersawa wood contain extractives which are more corrosive compared to other wood species tested. Mechanical wear  resistance is influenced by the abrasive material contained in the wood, especially silica, both in wood and wood composite products. Mersawa wood caused the cutting tools wear faster than other types of solid wood. Cement board as a composite product caused the damaged of the cutting edge of high speed steel tool due to high abrasive materials contained in the the cement board. Tungsten carbide tool has higher wear resistance than high speed steel tool.   Keywords : wear resistance, high speed steel, tungsten               carbide, silica, extractive